Recognition and Evaluation of Islamic Components in Business - Valipour, Abolfazl; Hashemi Nekoo, Seyed Alireza; Haghighat Monfared, Jalal (Business, Marketing, and Finance Open, 2025)
Religious tendencies within societies can significantly influence the success or failure of businesses. Various religions across the world shape distinct worldviews and ideologies that impact multiple aspects of their followers' lives, including business practices and organizational success. Islam, as the second most widely practiced religion globally, with over one billion adherents, extends its influence beyond the lives of Muslims to broader human interactions through social and economic networks. Among the key areas affected by religious values are business and entrepreneurship. This study examines Islamic business principles by reviewing scholarly sources, identifying Islamic variables and components, and designing a structured questionnaire. By collecting 51 responses from business experts and entrepreneurs, the research captures their perspectives on these variables. Statistical analysis was conducted using SPSS software, and the findings highlight the most influential Islamic components contributing to business success, with a particular focus on testamentary variables.